Efeitos do extrato de parede de levedura em dieta seca sobre a Microbiologia, ácidos graxos de cadeia curta e redução do odor das fezes de gatos adultos - Aquino, Adriana Augusto; Alves, Mariana Pereira; Santos, João Paulo Fernandes; Feliciano, Marcus Antônio Rossi [UNESP]; Piccoli, Roberta Hilsdorf; Saad, Flávia Maria de Oliveira Borges (FapUNIFESP (SciELO), 2012)
The aim of this study was to evaluate the effects of yeast cell wall extract (YCW) in dry diet on the fecal microbiota, concentration of short-chain fatty acids (SCFA) and on the odor reduction of cats feces. We used 20 animals of both sexes, randomly assigned to four treatments and five repetitions totaling 20 experimental units: 1) dry commercial diet (control); 2) control + 0.2%, 3) control + 0.4%, and 4) control + 0.6% of YCW in dry matter. Enterobacteriaceae and lactic acid bacteria, fecal concentration of acetic, propionic and butyric acids, ammonia nitrogen and sensory panel were performed. There were no significant differences (p> 0.05) for bacterial counts and the concentration of SCFA and ammonia, but in sensory panel a reduction in the odor of feces could be noted with the use of 0.2% of YCW. We concluded that the addition of up to 0.6% YCW had no effect on the microbiology and the concentration of fatty acids, but there is potential for its use as an additive because of the improvement in the odor of feces. However, further studies are needed to understand the mechanisms of action and the effects of prebiotics for domestic cats.
Effects of yeast cell wall extract in dry diet on Microbiology, short-chain fatty acids and fecal odor reduction of adult cats
Keywords: Ammoniacal nitrogen; Butyric acid; Feline; Lactic bacteria; Mannanoligosacharide; Animalia; Bacteria (microorganisms); Enterobacteriaceae; Felidae; Felis catus